Use of paracetamol during pregnancy and child neurological development. (7th April 2015) - de Fays, Laurence; Van Malderen, Karen; De Smet, Karen; Sawchik, Javier; Verlinden, Veerle; Hamdani, Jamila; Dogné, Jean‐Michel; Dan, Bernard
<x xml:space="preserve">Abstract</x> Paracetamol (acetaminophen) remains the first line for the treatment of pain and fever in pregnancy. Recently published epidemiological studies suggested a possible association between paracetamol exposure in utero and attention‐deficit–hyperactivity disorder/hyperkinetic disorder (ADHD/HKD) or adverse development issues in children. However, the effects observed are in the weak to moderate range, and limitations in the studies' design prevent inference on a causal association with ADHD/HKD or child neurological development. In parallel, recent animal data showed that cognition and behaviour may be altered following exposure to therapeutic doses of paracetamol during early development. These effects may be mediated by interference of paracetamol with brain‐derived neurotrophic factor, neurotransmitter systems (including serotonergic, dopaminergic, adrenergic, as well as the endogenous endocannabinoid systems), or cyclooxygenase‐2. However, no firm conclusion can be made on the relevance of these observations to humans. We conclude that additional well‐designed cohort studies are necessary to confirm or disprove the association. In the context of current knowledge, paracetamol is still to be considered safe in pregnancy and should remain the first‐line treatment for pain and fever.